2020
DOI: 10.7554/elife.54128
|View full text |Cite
|
Sign up to set email alerts
|

Monoubiquitination by the human Fanconi anemia core complex clamps FANCI:FANCD2 on DNA in filamentous arrays

Abstract: FANCI:FANCD2 monoubiquitination is a critical event for replication fork stabilization by the Fanconi anemia (FA) DNA repair pathway. It has been proposed that at stalled replication forks, monoubiquitinated-FANCD2 serves to recruit DNA repair proteins that contain ubiquitin-binding motifs. Here, we have reconstituted the FA pathway in vitro to study functional consequences of FANCI:FANCD2 monoubiquitination. We report that monoubiquitination does not promote any specific exogenous protein:protein interactions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 75 publications
1
61
0
Order By: Relevance
“…Metaphorically, this rotation closes the trough observed in apo-FANCI–FANCD2, clamping the complex on DNA. This conformational change significantly decreases the off-rate of FANCI–FANCD2 to dsDNA [ 21 , 24 ], which is the central event for DNA repair activation. The main finding of the present study is that the ubiquitin acts as a wedge to stabilize the FANCI–FANCD2 closed conformation on DNA [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Metaphorically, this rotation closes the trough observed in apo-FANCI–FANCD2, clamping the complex on DNA. This conformational change significantly decreases the off-rate of FANCI–FANCD2 to dsDNA [ 21 , 24 ], which is the central event for DNA repair activation. The main finding of the present study is that the ubiquitin acts as a wedge to stabilize the FANCI–FANCD2 closed conformation on DNA [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Four concurrent studies also demonstrated a requirement for FANCD2 Ub but not FANCI Ub in DNA clamping, for human, chicken and Xenopus homologs [ 21 , 24 , 25 , 33 ]. The cryo-EM structures of di-monoubiquitinated human FANCI–FANCD2 (FANCI Ub –FANCD2 Ub , PDB: 6VAE , 3.8 Å) reveals why this is the case ( Figure 2 B) [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations